Mortality in gastro-oesophageal reflux disease in a population-based nationwide cohort study of Swedish twins. Issue 8 (6th August 2020) - Ness-Jensen, Eivind; Santoni, Giola; Gottlieb-Vedi, Eivind; Lindam, Anna; Pedersen, Nancy; Lagergren, Jesper
Abstract : Objectives: The public health disorder gastro-oesophageal reflux disease (GORD) is linked with several comorbidities, including oesophageal adenocarcinoma (OAC), but whether life expectancy is reduced by GORD is uncertain. This study assessed all-cause and cancer-specific mortality in GORD after controlling for confounding by heredity and other factors. Design: Population-based cohort study from 1998 to 2015. Setting: Swedish nationwide study. Participants: Twins (n=40 961) born in 1958 or earlier in Sweden. Exposure: GORD symptoms reported in structured computer-assisted telephone interviews. Outcomes: The primary outcome was all-cause mortality and the secondary outcome was cancer-specific mortality among twins with GORD and twins without GORD. HRs and 95% CIs were analysed using parametric survival models, both in individual twin analyses and co-twin pair analyses, with adjustment for body mass index, smoking, education and comorbidity. Results: Among 40 961 individual twins, 5812 (14.2%) had GORD at baseline and 8062 (19.7%) died during follow-up of up to 16 years. The risks of all-cause mortality (HR=1.00, 95% CI: 0.94–1.07) and cancer-specific mortality (HR=0.99, 95% CI: 0.89–1.10) were not increased in individual twins with GORD compared with individual twins without GORD. Similarly, there were no differences in mortality outcomes in within-pair analyses. The OAC-specific mortality rate was 0.45 (95% CI: 0.32–0.66) per 1000 person-years in individual twins with GORD and 0.22 (95% CI: 0.18–0.27) per 1000 person-years without GORD, rendering an adjusted HR of 2.01 (95% CI: 1.35–2.98). Conclusions: GORD did not increase all-cause or cancer-specific mortality when taking heredity and other confounders into account. The increased relative risk of mortality in OAC was low in absolute numbers.